2001
DOI: 10.5194/angeo-19-1697-2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of natural plasma emissions observed close to the plasmapause by the Cluster-Whisper relaxation sounder

Abstract: Abstract. We use the data collected by the Whisper instrument onboard the Cluster spacecraft for a first test of its capabilities in the identification of the natural plasma waves observed in the Earth' s magnetosphere. The main signatures observed at the plasma frequency, upper hybrid frequency, and electron Bernstein modes were often difficult to be reliably recognized on previous missions. We use here the characteristic frequencies provided by the resonances triggered by the relaxation sounder of Whisper to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
(55 reference statements)
1
29
0
Order By: Relevance
“…In the passive mode, natural wave bands between two successive harmonics of the electron gyro-frequency can be observed. We used these active and passive measurements to obtain the electron density through the method specified by Canu et al (2001) and Trotignon et al (2001Trotignon et al ( , 2003. The density derived from the local measurement provided by WHISPER along the spacecraft orbit was used to derive the density along L shells using an R −4 model for the electron density (Persoon et al, 1983;Gallagher et al, 2000).…”
Section: Simulation Results: the Ray-tracing Techniquementioning
confidence: 99%
“…In the passive mode, natural wave bands between two successive harmonics of the electron gyro-frequency can be observed. We used these active and passive measurements to obtain the electron density through the method specified by Canu et al (2001) and Trotignon et al (2001Trotignon et al ( , 2003. The density derived from the local measurement provided by WHISPER along the spacecraft orbit was used to derive the density along L shells using an R −4 model for the electron density (Persoon et al, 1983;Gallagher et al, 2000).…”
Section: Simulation Results: the Ray-tracing Techniquementioning
confidence: 99%
“…Intense chorus was observed by the WBD, STAFF, and Whisper wave instruments. Plasma density of a few particles per cm 3 , indicative of magnetospheric regions outside the plasmasphere, was estimated from the Whisper data (P. Canu, private communication, 2002;Canu et al, 2001). The WBD instruments measured continuous waveforms with pass-band filters between 50 Hz and 9.5 kHz, mainly using the 88-m electric double-sphere antennas (for short periods of time, signals from magnetic search coil antennas were transmitted-these data are not shown here).…”
Section: Time-frequency Characteristics Of Chorus In the Source Regionmentioning
confidence: 99%
“…Trotignon et al (2001) explains how the WHISPER measurements can be used to determine electron density, and Canu et al (2001) discuss the natural plasma emissions observed close to the plasmapause. WHISPER data are extremely rich and the subject of ongoing interpretation, but the basic resonances observed in the ambient plasma include the plasma, electron gyro-, upper-hybrid, and Bernstein's mode frequencies.…”
Section: Cluster Satellite Observationsmentioning
confidence: 99%